RDA: a critical analysis based on cataloguing theory and practice - Alberto Petrucciani (JLIS.it, 2016)
RDA appears to be an hybrid standard: a list containing a high number of bibliographic elements and a rewrite - more formal than substantial - of cataloguing practices established with AACR2. In this document, RDA guidelines are analysed trying to compare them to the requirements of good cataloguing rules. Cataloguing rules in general shold not be an abstract and self-referential model but an effective tool to analyse and represent cultural phenomena, useful to qualified staff and helpful in learning about users need. From this point of view, RDA is quite disappointing: many relevant and frequent cataloguing issues are not mentioned at all, and cataloguing itself is left without real guidelines. A certain number of omissions, mistakes and individual flawness in the text should be modified by RDA board with a deep analysis of real cataloguing activities.